Republic of Palau : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Palau. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic and related containment measures have severely impacted the economy. Border closure and the suspension of commercial flights curtailed tourist arrivals. Real GDP contracted by 9.7 percent in FY2020, notwithstanding policy support. The economic contraction is estimated to have deepened in FY2021, and a gradual recovery is expected in FY2022 as tourism activities resume. While Palau's public debt remains sustainable, the economic fallout of the pandemic and the cost of the fiscal response have led to a sharp deterioration of the fiscal position and a rapid increase in public debt. The high share of concessional loans from multilateral creditors in Palau's external debt is an important risk mitigating factor. Palau is vulnerable to climate change and natural disasters.